Sanctions, Censure and Punitive Censorship: Some Targeted Hebrew Translations of Arabic Literature from 1961-1992 - Amit-Kochavi, Hannah (TTR, 2010)
Translations of Arabic literature into Hebrew have been marginally present in Israeli Jewish culture for the last 62 years. Their production and reception have been affected by the ongoing political Jewish-Arab conflict which depicts the Arab as a threatening enemy and inferior to the Jew. This depiction has often led to fear and apprehension of Arabic literary works. The present paper focuses on several cases where Hebrew translations of Arabic prose and poetry were publicly condemned as a potential threat to the stability of Israeli Jewish sociopolitical creeds and state security. The various sanctions imposed on the texts and their writers (though not on their translators!) by Israeli authorities, the Israeli Hebrew press and public opinion are described and explained. These sanctions were subsequently lifted after Israeli Jewish writers rose up against censure and censorship by raising their voices in protest.